Microeconomics anti-textbook - Myatt, Tony (London, England : Zed Books, 2018)
"Mainstream textbooks present economics as an objective science, free from value judgements. The Microeconomics Anti-Textbook demonstrates this to be a myth ? one which serves to make such textbooks not only off-puttingly bland, but also dangerously misleading in their justification of the status quo and neglect of alternatives. In this fully updated and expanded edition of their celebrated book, Professors Rod Hill and Tony Myatt lay out the essentials of each topic in the standard texts in a clear and concise way, before presenting an 'anti-text' analysis and critique. Challenging the assumptions, arguments, and models, Hill and Myatt provide the essential guide to decoding the textbooks, and show that real economics is far more interesting - and subversive - than the simplistic version presented to students."--
Introduction - Our Goals, Audience, and Principal Themes -- 1. What is economics? Where you start influences where you go -- 2. Introducing economic models -- 3. How markets work (in an imaginary world) -- 4. People as consumers -- 5. The firm -- 6. Market Structure and Efficiency - or why perfect competition isn't so perfect after all -- . Addendum - What about the efficiency of asset markets? -- 7. Externalities and the ubiquity of market failure -- 8. The marginal productivity theory of income distribution - or you're worth what you can get -- 9. Government, taxation, and the (re)distribution of income: is a just society just too expensive? -- 10. Trade and globalization without the rose-tinted glasses Conclusion Postscript - A Case Study on the Global Financial Meltdown
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Economics; Microeconomics; Critical thinking; Textbook bias; Microeconomics; Electronic books